Modern methods of monitoring and evaluating the current functional state of athletes in various types of martial arts - Volodymyr Revenko; Yaroslavna Puhach; Valeriy Druz; Vadym Artemiev (Kharkiv State Academy of Physical Culture, 2019)
Purpose: development of a contactless real-time monitoring system of the athlete's current functional state. Material & Methods: analysis of scientific and methodological literature on the problems of ongoing research; biomechanical analysis of the kinematic and dynamic characteristics of the athlete's motor actions when performing competitive exercises; methods of mathematical statistics; computer mathematical modeling. Results: the existing methods for assessing the functional state of the body during the training and competitive activities of the athlete are reviewed and analyzed, on the basis of which the requirements for the construction of a method of contactless monitoring of the athlete's functional state are determined. Conclusions: the functional state of martial arts athletes is currently monitored by modern equipment with a high degree of accuracy and speed of information processing, but only in contact mode, which excludes the possibility of operational monitoring of the athlete's current state during the fight. The study of the biomechanics of the motion of the kinematic links of the limbs and the static working pose based on the materials of the video recording of the athlete's movements made it possible to establish the dependence of the flow of dynamic forces that determine the speed of movement of the biokinematic pairs, which formed the basis of the developed non-contact method for assessing the measure of athlete fatigue directly during the fight. Modern techniques of video recording, computer support and established patterns of kinematic movements at various static stresses of the working pose allowed us to achieve our goal.